If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = p + -8 Reorder the terms: 14 = -8 + p Solving 14 = -8 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 14 + -1p = -8 + p + -1p Combine like terms: p + -1p = 0 14 + -1p = -8 + 0 14 + -1p = -8 Add '-14' to each side of the equation. 14 + -14 + -1p = -8 + -14 Combine like terms: 14 + -14 = 0 0 + -1p = -8 + -14 -1p = -8 + -14 Combine like terms: -8 + -14 = -22 -1p = -22 Divide each side by '-1'. p = 22 Simplifying p = 22
| 1/4t+1/3t=7/12 | | 0.05+0.01x=6x | | 2(x+3)=6x-12 | | 5(2x+3x)-20=55 | | 100-4x=20 | | 6x+3y=16 | | 100-4x= | | t^2=33 | | 3x+9=21x | | x+(x-6)+15=39 | | (X-1)(x+9)=0 | | 11.2t+2=4.7t+44.90 | | 9-4d=3 | | 2x+5y=-44 | | 2.1x+97=4.7x+6 | | x^2-4xy^2=0 | | 5(2x-1)+3(4-9x)=0 | | 12x-5=7x+60 | | 1x-8=-6x+6 | | 2x+3=4+6x | | 7(x-3)=84 | | 11f+6=12f+6 | | -2z+7=21 | | 8(3s+6)= | | uk+un=r | | 4(4-c)=3(5-c)+4 | | 10c+8=14c-20 | | 17=-b+6 | | 8(2l+1)= | | 6a-10=4a+2 | | 2(2w-6)+2(w)=3(w+8) | | 4(a-3)= |